Foreword - Abramowicz, Anete (Revista Eletrônica de Educação, 2015)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> DOI: http://dx.doi.org/10.14244/198271991221 Foreword Dossier on Childhood and Ethnic-Racial Relations <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->